Tranexamic acid: Beyond antifibrinolysis. (14th July 2022) - Prudovsky, Igor; Kacer, Doreen; Zucco, Victoria Vieira; Palmeri, Monica; Falank, Carolyne; Kramer, Robert; Carter, Damien; Rappold, Joseph
Abstract: Tranexamic acid (TXA) is a popular antifibrinolytic drug widely used in hemorrhagic trauma patients and cardiovascular, orthopedic, and gynecological surgical patients. TXA binds plasminogen and prevents its maturation to the fibrinolytic enzyme plasmin. A number of studies have demonstrated the broad life‐saving effects of TXA in trauma, superior to those of other antifibrinolytic agents. Besides preventing fibrinolysis and blood loss, TXA has been reported to suppress posttraumatic inflammation and edema. Although the efficiency of TXA transcends simple inhibition of fibrinolysis, little is known about its mechanisms of action besides the suppression of plasmin maturation. Understanding the broader effects of TXA at the cell, organ, and organism levels are required to elucidate its potential mechanisms of action transcending antifibrinolytic activity. In this article, we provide a brief review of the current clinical use of TXA and then focus on the effects of TXA beyond antifibrinolytics such as its anti‐inflammatory activity, protection of the endothelial and epithelial monolayers, stimulation of mitochondrial respiration, and suppression of melanogenesis.